SC26 The impact of monthly multimodal theme-based postgraduate education in a busy obstetrics and gynaecology department. (November 2018) - Egbase, Elizabeth; Ferns, Janis; Thamban, Sujatha; Elliot, Jennifer; Clarke, Nick; Saddiq, Surajat
Abstract : Background: Educational psychology shows learning is a process of integration; learners connect facts and ideas to construct meaning. The current shift-based structure of the NHS has negatively affected post graduate medical education and training in specialities with high out of hours workloads. The 2010 Temple Report recommends making 'every moment count' highlighting the benefits of using clinical cases and simulation-based training to accelerate learning. The challenge is to establish and integrate high quality, acceptable and accessible post-graduate medical education within a busy department. Programme: 'Monthly Educational Theme (MET)' is a pilot theme-based education programme currently running at Whipps Cross Hospital which delivers 5000 babies a year. Themes are aligned with The Royal College of Obstetricians and Gynaecology curriculum, and learning outcomes from serious incidents as means of embedding change of practice through training. The programme is distributed at the start of the month, comprising of weekly didactic lectures on guidelines or cases, bi-monthly journal club and simulation -based training. Teaching is delivered by junior doctors and simulation facilitators who have expertise in this modality. The educational themes to date are: Hypertension; Sepsis; Haemorrhage; Fertility and Intrapartum care. Results: The programme has recently been embedded and data from April 2018 where the theme was 'Think Intrapartum Care' has been analysed. There were 41 doctors working in the Obstetrics and Gynaecology department, 66.8% attended at least one teaching session with 47% attending more than half of the teaching sessions. All sessions had attendance from the Multidisciplinary team and with midwives comprising 79% of attendance at simulation based training this month. The simulation sessions were highly rated: 90% strongly agreed that the session met their learning needs and 73% strongly agreed the session were a catalyst for reflection on their practice. Discussion: Initial results suggest that sessions are high quality and the theme-based programme is well received. Thematic learning allows for integration of concepts within various learning experiences. The multimodality appeals to all learning styles. Advantages of theme-based teaching are well documented enabling learning to extend beyond individual sessions. Junior doctors delivering teaching creates a community of learners and because topics are clinically relevant, participants are able to construct individualised meaning from the content. Simulation fosters active experimentation and application to clinical practice. This pilot project is improving access, acceptability and quality of medical education and training, further research into its long-term effectiveness and reliability as an educational programme is planned. References: Temple J. Time for training: A review of the impact of the European working time directive on the quality of training 2010. London: Medical Education England. Czerniak CM, Lumpe AT, Haney JJ. Science teachers' beliefs and intentions to implement thematic unit. Journal of Science Teacher Education1999;10:123. Available from: https://doi.org/10.1023/A:1009424015197